The Design of Static Test Scheme for Composite Aileron Structure of Large Aircraft. Issue 1 (March 2021) - Zhang, Guanbiao; Liu, Shuaicai; Zhang, Limeng; Zhang, Jiying
Abstract: According to the load conditions and structural features of composite aileron structure of large aircraft, the design techniques of full-scale static test scheme of aileron is studied, which can be used to examine the static strength and verify the airworthiness compliance of aileron structure. The overall test scheme design was carried out from the aspects of test load, test support, damage introduction and measurement scheme, and created a set of test design processes that meet the requirements of airworthiness. Loads screening was carried out by using strain coverage principle, the aerodynamic loads were transformed into test load by coordinate transformation. The wing was used as the aileron test support section, and a ground support device can also be designed to carry out aileron bench test. The introduction mode of aileron structure damage was defined, including the type, location and size. A reasonable layout of strain and displacement sensors was given for test measurement. Test results showed that the static test scheme in this paper can be used for the airworthiness compliance verification of static strength of aileron structure.